Strategi Proses Pelaksanaan Guru Pendidikan Agama Islam di SMP Negeri 35 Medan - Arlina, Arlina; Hakim, Arif Rahman; Sitorus, Nur Ikhsan Kharisma; Asiah, Nur; Gultom, Siti Nurjannah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to find out how Islamic education teachers teach 9th grade students at SMPN 35 Medan, Jln. Tegal Sari Dusun VI Tembung, Kec. Percut Sei Tuan, Kab. Deli Serdang, North Sumatra. The research method used qualitative. The descriptive data obtained consists of words, descriptions, and behaviors expressed in the form of reports. This is done through data collection, data interpretation, drawing conclusions, and reporting. The research results show that the teaching strategies used by Islamic education teachers for 9th grade students at SMPN 35 Medan involve several stages. Before starting the Islamic education lesson, the teacher greets the students with a greeting. Then, the teacher directs the students to recite a prayer together led by one of the male students. After that, the teacher takes attendance. Then, the teacher briefly explains the material to be discussed. Next, the teacher divides the students into several groups consisting of 4-5 people. The teacher then directs the students to read supporting books related to the material being studied, and finally, the teacher creates a game aimed at increasing the students' knowledge and rewards the group that wins.